Natural Products Containing Olefinic Bond: Important Substrates for Semi-synthetic Modification Towards Value Addition - Singh, Meenakshi; Ravichandiran, V.; Bharitkar, Yogesh P.; Hazra, Abhijit (Current Organic Chemistry, 2020)
Semi-synthesis, the way of preparing novel bioactive molecules via modification of compounds isolated from natural sources is very much useful nowadays in the drug discovery process. The modification is based on the reaction of functional group(s) present in a natural compound. Among the examples of functional group transformation, double bond modification is also common in the literature. Several reactions like hydrogenation, cyclopropanation, epoxidation, addition reaction (halogenations, hydroxylation), Michael addition, Heck reaction, cycloaddition, dipolar cycloaddition, etc. are employed for this purpose. In this review, we have tried to gather the reactions performed with several double bond containing classes of natural products like diterpenes, xanthones, sesquiterpene exomethylene lactones, diaryl heptanoids, steroidal lactones, triterpenoids, limonoids, and alkamides. Where available, the effects of transformations on the biological activities of the molecules are also mentioned.
Keywords: double bond